How do compression and flexion-compression injuries destabilize the spine? A novel in vitro protocol for analyzing three-dimensional biomechanical instability - Greiner-Perth, Ann-Kathrin; Wilke, Hans-Joachim; Liebsch, Christian (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionUnstable traumatic spinal injuries require surgical stabilization. However, biomechanical instability of specific spinal injuries has been little investigated, although restoring stability represents a primary goal of surgical treatment. This study aimed (1) to develop an in vitro protocol to generate standardized spinal compression injuries, (2) to establish a three-dimensional flexibility analysis to identify relevant biomechanical instability parameters, and (3) to examine effects of person-specific factors on vertebral fragility.MethodsMechanical fracture simulation was performed on twelve fresh-frozen human spine specimens (T9-11; 4 f/8 m; 40–60 years) using a material testing machine. Pure compression trauma (n = 6) was simulated by applying displacement-controlled axial compression at 300 mm/s until 20% compression of the T10 vertebral body height. Flexion-compression trauma (n = 6) was achieved by additional flexural loading of 10 Nm. Pre- and post-traumatic pure moment testing with 5 Nm was performed in flexion/extension, lateral bending, and axial rotation using optical motion tracking to determine range of motion (ROM), neutral zone (NZ), coupled rotations, and coupled translations. Translations under shear loading of 100 N and axial deformation under 400 N compression were analyzed.ResultsAll specimens exhibited AOSpine A1 injuries occurring at a median fracture load of 5.0 kN (2.4–9.2 kN). Pure compression generated isolated medial endplate fractures (n = 5), while flexion-compression primarily provoked combined endplate and ventral compression injuries (n = 3). Significant (p < 0.05) increases were detected for all parameters except for coupled rotations and posterior (compression) and left shear translation (flexion-compression). Highest instability increases were determined for axial deformability (compression: +136% / flexion-compression: +200%) and NZ (flexion/extension: +177% / 188%; lateral bending: +174% / +126%). Mild to moderate disc degeneration and age did not correlate with fracture loads (p > 0.05). In compression trauma, cortical bone mineral density (BMD) of T10 had no effect on fracture loads (p > 0.05), whereas in flexion-compression trauma, a significant (p < 0.05) linear correlation was found (Spearman’s rs = 0.83).DiscussionRelevant instability parameters of minor compression and flexion-compression injuries include axial deformability, NZ, ROM, and coupled translations. Cortical BMD of the target vertebra solely affects fracture generation in flexion-compression trauma. Consequently, risk factors for fracture development may vary between trauma mechanisms.